Groups and Protocluster Candidates in the CLAUDS and HSC-SSP Joint Deep Surveys - Li, Qingyang; Yang, Xiaohu; Liu, Chengze; Jing, Yipeng; He, Min; Huang, Jia-Sheng; Dai, Y. Sophia; Sawicki, Marcin; Arnouts, Stephane; Gwyn, Stephen; Moutard, Thibaud; Mo, H. J.; et al. (The Astrophysical journal, 2022)
Using the extended halo-based group finder developed by Yang et al., which is able to deal with galaxies via spectroscopic and photometric redshifts simultaneously, we construct galaxy group and candidate protocluster catalogs in a wide redshift range (0 < z < 6) from the joint CFHT Large Area U -band Deep Survey and Hyper Suprime-Cam Subaru Strategic Program deep data set. Based on a selection of 5,607,052 galaxies with i -band magnitude m i < 26 and a sky coverage of 34.41 deg 2 , we identify a total of 2,232,134 groups, of which 402,947 groups have at least three member galaxies. We have visually checked and discussed the general properties of these richest groups at redshift z > 2.0. By checking the galaxy number distributions within a 5–7 h −1 Mpc projected separation and a redshift difference Δ z ≤ 0.1 around those richest groups at redshift z > 2, we identify lists of 761, 343, and 43 protocluster candidates in the redshift bins 2 ≤ z < 3, 3 ≤ z < 4, and z ≥ 4, respectively. In general, these catalogs of galaxy groups and protocluster candidates will provide useful environmental information in probing galaxy evolution along cosmic time.